Oral and maxillofacial pathology - Neville, Brad W.; Neville, Brad W (St. Louis, Mo. : Saunders/Elsevier, 2009)
From the Publisher: Be prepared to diagnose and manage any condition you encounter in your practice! This bestselling reference gives you direct access to a complete range of full-color clinical images and patient radiographs that illustrate the differentiating characteristics of lesions in the oral and maxillofacial region. Significantly revised and updated content throughout this edition brings you the latest information on the etiology, clinical features, histopathology, treatment, and prognosis of each disease entity, as well as cutting-edge topics such as bisphosphonate osteonecrosis, the oral complications associated with methamphetamine abuse, solitary fibrous tumors, gene mutation, and plasminogen deficiency. Over 1,300 clinical photos and radiographs, most in full color, facilitate identification and classification of lesions. Current concepts of pathogenesis and disease management help you understand the diseases that affect the oral and maxillofacial structures, formulate an accurate diagnosis, and institute proper treatment. Each chapter is logically organized by body system or disease group, enabling you to easily identify a specific condition. A comprehensive appendix of differential diagnosis among oral and maxillofacial disease processes helps you rule out invalid diagnoses. The bibliography divided by topic presented at the end of each chapter enables you to pursue supplemental literature. Highly accomplished authors and contributors with a broad range of clinical and classroom teaching experience provide well-balanced coverage of the entire subject. Chapter outlines at the beginning of each chapter allow immediate access to specific topics. Over 200 new illustrations have been added to this popular, visual reference. A new section on bisphosphonate-associated osteonecrosis thoroughly explores and illustrates this recently identified complication resulting from medications used to prevent bone loss in patients with multiple myeloma, metastatic tumors, and osteoporosis. A new section about the oral complications of methamphetamine abuse details characteristic oral manifestations such as "meth mouth caries" and factitial injuries. Expanded coverage of oral piercings, intraoral tattoos, and other body modifications includes unusual entities such as tongue splitting and charm needles. A new section on transient lingual papillitis sheds light on this common cause of transitory tongue irritation. A new section on solitary fibrous tumors familiarizes you with this popular designation for certain benign fibrous neoplasms. A new section on hypoplasminogenemia (ligneous conjunctivitis), or plasminogen deficiency, includes images from a patient case that illustrate the characteristic gingival lesions associated with this rare but fascinating systemic condition. A new section on hereditary mucoepithelial dysplasia describes the characteristic oral manifestations that can lead you to accurately diagnose this condition, potentially preventing a woman with this disorder from having cytologically unusual cells misdiagnosed as carcinoma on her cervical PAP smears. A new section discusses the clinical and microscopic features of chronic ulcerative stomatitis, an immune-mediated condition of the oral mucosa that presents with erosive lesions and is often mistaken for lichen planus. The chapter on Forensic Dentistry has been thoroughly revised and updated by leading forensic odontology author, Dr. Edward Herschaft, to include the latest information on this fascinating topic. Several chapters have been updated to include the most current knowledge of specific gene mutations associated with hereditary oral disorders
8: Physical And Chemical Injuries -- Linea alba -- Morsicatio buccarum -- Traumatic ulcerations -- Electrical and thermal burns -- Chemical injuries of the oral mucosa -- Noninfectious oral complications of antineoplastic therapy -- Bisphosphonate-associated osteonecrosis -- Orofacial complications of methamphetamine abuse -- Anesthetic necrosis -- Exfoliative cheilitis -- Submucosal hemorrhage -- Oral trauma from sexual practices -- Amalgam tattoo and other localized exogenous pigmentations -- Oral piercings and other body modifications -- Systemic metallic intoxication -- Smoker's melanosis -- Drug-related discolorations of the oral mucosa -- Reactive osseous and chondromatous metaplasia -- Oral ulceration with bone Sequestration -- Pseudocysts and cysts of the maxillary sinus -- Cervicofacial emphysema -- Mysopherulosis -- 9: Allergies And Immunologic Diseases -- Transient lingual papillitis -- Recurrent aphthous stomatitis -- Behcet's syndrome -- Sarcoidosis -- Orofacial granulomatosis -- Wegener's granulomatosis -- Allergic mucosal reactions to systemic drug administration -- Allergic contact stomatitis -- Perioral dermatitis -- Contact stomatitis from artificial cinnamon flavoring -- Lichenoid contact stomatitis from dental restorative materials -- Angioedema -- 10: Epithelial Pathology / revised by Angela C Chi -- Squamous papilloma -- Verruca vulgaris -- Condyloma acuminatum -- Multifocal epithelial hyperplasia -- sinonasal papillomas -- Molluscum contagiosum -- Verruciform xanthoma -- Seborrheic keratosis -- Sebaceous hyperplasia -- Ephelis -- Actnic lentigo -- Lentigo simplex -- Melsma -- Oral melanotic mascule -- Oral melanoacanthoma -- Acquired melanocytic nevus -- Variants of melanocytic nevus -- Leukoplakia -- Erythroplaskia -- Smokeless tobacco use and smokeless tobacco keratosis -- Oral submucous fibrosis -- Nicotine stomatitis -- Actinic keratosis -- Actinic cheilosis -- Keratoacanthoma -- Squamous cell carcinoma -- Verrrucous carcinoma -- Spindle cell carcinoma -- Adenosquamous carcinoma -- Basaloid squamous carcinoma -- Carcinoma of the maxillary sinus -- Sinonasal undifferentiated carcinoma -- Nasopharyngeal carcinoma -- Basal cell carcinoma -- Merkel cell carcinoma -- Melanoma -- 11: Salivary Gland Pathology -- Salivary gland aplasia -- Mucocele -- Ranula -- Salivary duct cyst -- Sialolithiasis -- Sialadenitis -- Cheilitis glandularis -- Sialorrhea -- Xerostomia -- Benign lymphoepithelial lesion -- Sjogren syndrome -- Sialadenosis -- Adenomatoid hyperplasia of the minor salivary glands -- Necrotizing sialometaplasia -- Salivary gland tumors -- General considerations -- Pleomorphic adenoma -- Oncocytoma -- Oncocytosis -- Warthin tumor -- Monomorphic adenoma -- Canalicular adenoma -- Basal cell adenoma -- Ductal papillomas -- Mucoepidermoid carcinoma -- Intraosseous mucopeidermoid carcinoma -- Acinic cell adenocarcinoma -- Malignant mixed tumors -- Adenoid cystic carcinoma -- Polymorphous low-grade adenocarcinoma -- Salivary adenocarcinoma not otherwise specified -- 12: Soft Tissue Tumors -- Fibroma -- Giant cell fibroma -- Epulis fissuratum -- Inflammatory papillary hyperplasia -- Fibrous histiocytoma -- Fibromatosis -- Myofibroma -- Oral focal mucinosis -- Pyogenic granuloma -- Peripheral giant cell granuloma -- Peripheral ossifying fibroma -- Lipoma -- Traumatic neuroma -- Palisaded encapsulated neuroma -- Neurilemoma -- Neurofibroma -- Neurofibromatosis type I -- Multiple endocrine neoplasia type 2B -- Melanotic neuroectodermal tumor of infancy -- Paraganglioma -- Granular cell tumor -- Congenital epulis -- Hemangioma and vascular malformations -- Sturge-Weber angiomatosis -- Nasopharyngeal angiofibroma -- Hemangiopericytoma-solitary fibrous tumor -- Lymphangioma -- Leiomyoma -- Rhabdomyoma -- Osseous and cartilaginous choristomas -- Soft tissue sarcomas -- Fibrosarcoma -- Malignant fibrous histiocytoma -- Liposarcoma -- Malignant peripheral nerve sheath tumor -- Olfactory neuroblastoma -- Angiosarcoma -- Kaposi's sarcoma -- Leiomyosarcoma -- Rhabdomyosarcoma -- Synovial sarcoma -- Alveolar soft-part sarcoma -- Metastases to the oral soft tissues -- 13: Hematologic Disorders -- Lymphoid hyperplasia -- Hemophilia -- Plasminogen deficiency -- Anemia -- Sickle cell anemia -- Thalassemia -- Aplastic anemia -- Neutropenia -- Agranulocytosis -- Cyclic neutropenia -- Thrombocytopenia -- Polycythemia vera -- Leukemia -- Langerhans cell histiocytosis -- Hodgkin's lymphoma -- Non-Hodgkin's lymphoma -- Mycosis fungoides -- Burkitt's lymphoma -- Extranopdal NK/T-cell lymphoma, nasal-type -- Multiple myeloma -- Plasmacytoma -- 14: Bone Pathology / revised by Angela C Chi -- Osteogenesis imperfacta -- Osteopetrosis -- Cleidocranial dysplasia -- Focal osteoporotic marrow defect -- Idiopathic osteosclerosis -- Massive osteolysis -- Paget's disease of bone -- Central giant cell granuloma -- Cherubism -- Simple bone cyst -- Aneurysmal bone cyst -- Fibro-osseous lesions of the jaws -- Fibrous dysplasia -- Cemento-osseous dysplasias -- Familial gigantiform cementoma -- Ossifying fibroma -- Juvenile ossifying fibroma -- Osteoma -- Gardner syndrome -- Osteoblastoma and osteiod osteoma -- Cementoblastoma -- Chondroma -- Chondromyxoid fibroma -- Synovial chondromatosis -- Desmoplastic fibroma -- Osteosarcoma -- Chondrosarcoma -- Ewing sarcoma -- Metastatic tumors to the jaws -- 15: Odontogenic Cysts And Tumors -- Odontogenic cysts -- Dentigerous cyst -- Eruption cyst -- Primordial cyst -- Odontogenic keratocyst -- Orthokeratinized odontogenic cyst -- Nevoid basal cell carcinoma syndrome -- Gingival (alveolar) cyst of the newborn -- Gingival cyst of the adult -- Lateral periodontal cyst -- Calcifying odontogenic cyst -- -- Glandular odontogenic cyst -- Buccal bifurcation cyst -- Carcinoma arising in odontogenic cysts -- Odontogenic tumors -- Tumors of odontogenic epithelium -- Ameloblastroma -- Malignant ameloblastoma and ameloblastic carcinoma -- Clear cell odontogenic carcinoma -- Adenomatoid odontogenic tumor -- Calcifying epithelial odontogenic tumor -- Squamous odontogenic tumor -- Mixed odontogenic tumors -- Ameloblastic fibroma -- Ameloblastic fibro odontoma -- Ameloblastic fibrosarcoma -- Odontoameloblastoma -- Odontoma -- Tumors of odontogenic ectomesenchyme -- Central odontogenic fibroma -- Peripheral odontogenic fibroma -- Granular cell odontogenic tumor -- Odontogenic myxoma -- Cementoblastoma -- 16: Dermatologic Diseases -- Ectodermal dysplasia -- White sponge nevus -- Hereditary benign intraepithelial dyskeratosis -- Pachyonychia congenita -- Dyskeratosis congentia -- Xeroderma pigmentosum -- Hereditary mucoephithelial dysplasia -- Incontinentia pigmenti -- Darier's disease -- Warty dyskeratoma -- Peutz-Jeghers syndrome -- Hereditary hemorrhagic telangiectasia -- Ehlers-Danlos syndromes -- Tuberous sclerosis -- Multiple hamartoma syndrome -- Epidermolysis bullosa -- Immune-mediated diseases and their evaluation -- Pemphigus -- Paraneoplastic pemphigus -- Mucous membrane pemphigoid -- Bullous pemphigoid -- Erythema multiforme -- Erythema migrans -- Reactive arthritis -- Lichen planus -- Chronic ulcerative stomatitis -- Graft-versus-host disease -- Psoriasis -- Lupus erythematosus -- Systemic sclerosis -- CREST syndrome -- Acanthosis nigricans -- 17: Oral Manifestations Of Systemic Diseases -- Mucopolysaccharidosis -- Lipid reticuleondothelioses -- Lipoid proteinosis -- Jaundice -- Amyloidosis -- Vitamin deficiency -- Iron-deficiency anemia -- Plummer-Vinson syndrome -- Pernicious anema -- Pituitary dwarfism -- Gigantism -- Acromegaly -- Hypothyroidism -- Hyperthyroidism -- Hypoparathyroidism -- Pseudohypoparathyroidism -- Hyperparathyroidism -- Hypercortisolism -- Addison's disease -- Diabetes mellitus -- Hypophosphatasia -- Vitamin D-resistant rickets -- Crohn's disease -- Pyostomatitis vegetans -- Uremic stomatitis -- 18: Facial Pain And Neuromuscular Diseases / revised by Theresa S Gonzales -- Bell's palsy -- Trigeminal neuralgia -- Glossopharyngeal neuralgia -- Postherpetic neuralgia -- Atypical facial pain -- Neuralgia-inducing cavitational osteonecrosis -- Cluster headache -- Paroxysmal hemicrania -- Migraine -- Temporal arteritis -- Myasthenia gravis -- Motor neuron disease -- Burning mouth syndrome -- Dysgeusia and hypogeusia -- Frey syndrome -- Osteoarthritis -- Rheumatoid arthritis -- Temporomandibular joint dysfunction -- Temporomandibular joint ankylosis -- 19: Forensic Dentistry / Edward E Herschaft -- Record management -- Identification -- Bite pattern evidence -- Human abuse -- Dentists as expert witnesses -- Summary -- Appendix: Differential Diagnosis Of Oral And Maxillofacial Diseases -- Part 1: Mucosal and soft tissue pathology: color changes -- Part 2: Mucosal and soft tissue pathology: surface alterations -- Part 3: Mucosal and soft tissue pathology: masses or enlargements -- Part 4: Radiographic pathology -- Part 5: Pathology of teeth -- Index
Includes bibliographical references and index
Keywords: Mouth -- Diseases; Teeth -- Diseases; Maxilla -- Diseases; Mouth Diseases -- pathology; Jaw Diseases -- pathology; Maxillofacial Injuries -- pathology; Tooth Diseases -- pathology